Re-imagining Child Protection towards humane social work with families - Featherstone, Bríd 1956-; White, Sue 1961-; Morris, Kate 1962- (Policy Press, 2014)
This book challenges the current child protection culture and calls for family-minded humane practice where children are understood as relational beings, parents are recognized as people with needs and hopes, and families are seen as carrying extraordinary capacities for care and protection
Title from publisher's bibliographic system (viewed on 03 Feb 2022)
Keywords: Child welfare / Great Britain